Impact of Hydroxylation and Hydration on the Reactivity of α‐Fe2O3 (0001) and (11¯02) Surfaces under Environmental and Electrochemical Conditions. Issue 21 (10th May 2018) - Noh, Junghyun; Li, Hong; Osman, Osman I.; Aziz, Saadullah G.; Winget, Paul; Brédas, Jean‐Luc
Abstract: Hematite (α‐Fe2 O3 ) is widely used as a catalytic electrode material in photo‐electrochemical water oxidation, where its surface compositions and stabilities can strongly impact the redox reaction process. Here, its surface configurations in environmental or electrochemical conditions are assessed via density functional theory (DFT) calculations conducted at the Perdew, Burke, and Ernzerhof (PBE)+ U level. The most energetically favorable surface domains of α‐Fe2 O3 (0001) and (1 1 ¯ 02) are predicted by constructing the surface phase diagrams in the framework of first‐principle thermodynamics. The relative surface stabilities are investigated as a function of partial pressures of oxygen and water, temperature, solution pH, and electrode potential not only for perfect bulk terminations but also for defect‐containing surfaces having various degrees of hydroxylation and hydration. In order to assess the impact on the redox reactions of the surface planes as well as of the extent of surface hydration/hydroxylation, the thermodynamics of the four‐step oxygen evolution reaction (OER) mechanism are examined in detail for different models of the α‐Fe2 O3 (0001) and (1 1 ¯ 02) surfaces. Importantly, the results underline that the nature of the surface termination and the degree of near‐surface hydroxylation give rise to significant variations in the OER overpotentials. Abstract : The water‐exposed (0001) and (1 1 ¯ 02) surfaces of hematite have been investigated at the Density Functional Theory level under varying environmental and electrochemical conditions. The results underline that the surface stoichiometry greatly impacts not only the near‐surface geometries and electronic structures but also the energetics of the oxygen evolution reaction, and thus plays a prominent role in hematite catalytic activity.